Demystifying archival projects five essentials for success - Note, Margot (Vancouver, British Columbia, Canada Lucidea Press, 2019)
"Demystifying Archival Projects: Five Essentials for Success will benefit archivists who lead or participate in projects without formal project management training. As work in archives continues to become more project-driven, educational and professional development opportunities for archivists have not kept pace. This book aims to provide the needed information--just enough project management methodology--to bridge that knowledge gap."--Back cover
Introduction -- Chapter 1: Initiating Archival Projects -- Chapter 2: Planning Archival Projects -- Chapter 3: Executing Archival Projects -- Chapter 4: Monitoring Archival Projects -- Chapter 5: Closing Archival Projects -- Conclusion -- Further Reading -- Glossary -- Templates.
Keywords: Archives -- Administration; Project management